Growth and Development of CSR – Corporate Social Responsibility in Europe (International Journal of Scientific Research and Management (IJSRM), 2017)
This research paper traces the historical evolution of the concept of CSR – Corporate Social Responsibility in the European perspectives. The duration covered under this research work comprises of a period of seventeen years, starting from 1990 to 2007. It chronologically highlights the growth and development that had taken place in different parts of Europe in the areas of CSR. The timeline of this research illustrates Europe’s pioneering role in the European CSR movement and strategy, from the European Business Declaration against Social Exclusion in the 1990s until the year 2007, the formation and development of the European Alliance for CSR